Branchless Banking in Pakistan : A Laboratory for Innovation - Bold, Chris (Washington, DC: World Bank, 2012)
Pakistan is one of the fastest developing markets for branchless banking in the world. Clear regulations and a regulator that is willing to both listen to the private sector and provide incentives for innovation have promoted a dynamic branchless banking sector. Two players have already launched services, and others are waiting in the wings. This brief highlights both existing and anticipated businesses and outlines the key challenges and opportunities that are likely to shape the market over the next twelve months.